2007
DOI: 10.1124/dmd.106.014100
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylclivorine: A Gender-Selective Metabolite of Clivorine Formed in Female Sprague-Dawley Rat Liver Microsomes

Abstract: ABSTRACT:Clivorine, a naturally occurring pyrrolizidine alkaloid, causes liver toxicity via its metabolic activation to generate toxic metabolite (pyrrolic ester). Female Sprague-Dawley (SD) rats are reported to be less susceptible to clivorine intoxication than male SD rats. However, the biochemical mechanism causing such gender difference is largely unknown. The present study investigated hepatic microsomal metabolism of clivorine in female rats to delineate the mechanism of the gender difference. Two pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 30 publications
0
79
2
1
Order By: Relevance
“…The species-, strain-or gender-depending variations in enzymatic activities or expressions, resulting in different overall balances of the detoxification and activation pathways, can influence the higher susceptibility of certain animals (e.g. male rat > guinea pig) to PA toxicity (Huan et al, 1998a;Lin et al, 2002Lin et al, , 2003Chung and Buhler, 2004;Lin et al, 2007).…”
Section: Metabolismmentioning
confidence: 99%
“…The species-, strain-or gender-depending variations in enzymatic activities or expressions, resulting in different overall balances of the detoxification and activation pathways, can influence the higher susceptibility of certain animals (e.g. male rat > guinea pig) to PA toxicity (Huan et al, 1998a;Lin et al, 2002Lin et al, , 2003Chung and Buhler, 2004;Lin et al, 2007).…”
Section: Metabolismmentioning
confidence: 99%
“…This finding implies that the esterase(s) present in our microsomal incubation system might be different isoforms specially targeted for the acetyl substituent. Similarly, a recent study (Lin et al, 2007) showed that clivorine could undergo deacetylation by PMSF-sensitive microsomal hydrolase A, suggesting a possible detoxification pathway in female rats. In our study, M1 and M2 were deacetylated metabolites of isoline, with formation inhibited dose dependently in mice by either TOCP or PMSF.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the liver microsomal fraction contains the highest activity of esterase(s), but there are large species differences, especially among small laboratory animals. Although the corresponding isoform in mouse (MH1) could be found with homology and characteristics similar to those of rat hydrolase A (Satoh and Hosokawa, 1998;Lin et al, 2007), further research to verify its identity and functions is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations